Chemical Composition, Antimicrobial and Anti-inflammatory Activity of Algerian Juniperus phoenicea Essential Oils - Abdelli, Wafae; Bahri, Fouad; Höferl, Martina; Wanner, Juergen (My University, 2018)
The essential oils (EOs) obtained by steam distillation from the leaves and the berries of Juniperus phoenicea L., harvested in northwest of Algeria were analyzed and their antimicrobial and anti-inflammatory activities were assessed. 63, 46 and 78 volatile compounds were identified by GC-FID and GC-MS from fresh leaves, dried leaves and berries representing 98.1%, 98.3% and 96.4% of the total oil, respectively. The fresh and dried leaves oils were mainly composed of β-phellandrene (43.9% / 44.9%), α -pinene (25.1% / 20.3%), myrcene (8.5% / 8.2%), α-phellandrene (4.7% / 4.5%) p-cymene (2.7% - 3.0%) and limonene (2.3% - 2.5%) whereas, the berries oil was mainly composed of α -pinene (43.7%), p-cymene (5.8%), β -phellandrene (4.6%), α-terpineol (4.3%) and α-campholenal (4.0%). The study of the antimicrobial activity showed that the 3 EOs were effective only on B. cereus ATCC 10876 and C. albicans ATCC 10231. No signs of acute toxicity have been noted in mice even at the highest dose tested (5000 mg/kg p.o). The fresh leaves, dried leaves and berries oils reduced the carrageenan-induced paw edema in mice by 16.8%, 15.2% and 6.4%, respectively, after 6 hours at a dose of 400 mg/kg p.o.
Keywords: Juniperus phoenicea, Essential oil, Chemical composition, Antimicrobial activity, Acute toxicity, Anti-inflammatory activity.